AB0117 CADHERIN-11 MRNA expression is increased in the peripheral blood of patients with active spondylarthropathy: a pilot study. (15th June 2017) - Vlachogiannis, NI; Christopoulos, PF; Bamias, G; Fragiadaki, K; Tektonidou, M; Sfikakis, PP
Abstract : Background: Cadherin-11 is a key regulator of synovial architecture and has a central role in the formation of the rheumatoid pannus. Immunohistochemical studies have shown upregulation of cadherin-11 in the synovium of patients with seronegative spondylarthropathies (SpA), comparable to that in rheumatoid arthritis (RA), as well as in the intestinal tissue of patients with inflammatory bowel disease (IBD). Moreover, cadherin-11 mRNA transcripts have been identified in the peripheral blood of patients with RA and independently associated, among various disease characteristics, with the presence of active inflammation in multiple joints [1]. Objectives: To test the hypothesis that cadherin-11 mRNA transcripts are increased in the peripheral blood of patients with active SpA and search for possible associations with clinical features. Methods: Fifteen patients with active SpA (BASDAI>4), aged between 21 and 71 years, 11 men, and 30 age- and gender-matched healthy controls were examined. Peripheral whole blood samples (3 ml) were subjected to cDNA synthesis and cadherin-11 mRNA expression was quantified by real-time PCR. Available cDNA from 33 IBD patients without axial or peripheral active arthritis served as disease control and were studied in parallel. Results: Cadherin-11 mRNA was detected in the peripheral blood of 9/15 (60%) patients with SpA versus 5/30 (17%) healthy controls and 10/33 (30%) patients with IBD (SpA vs healthy controls p: 0.006, SpA vs IBD p: 0.06). Notably, cadherin-11 was not associated with BASDAI or skin/nail psoriasis present in 10 patients, but was detected with increased frequency among SpA patients with clinically active peripheral arthritis at the time of sampling (7 out of 10, 70%) than the remaining patients (2 out of 5, 40%). Moreover, cadherin-11 positivity associated significantly with increased erythrocyte sedimentation rate in SpA but not in IBD. Conclusions: Cadherin-11 mRNA is upregulated in the peripheral blood of patients with SpA and may correlate with "spreading" of inflammation in peripheral joints. Since an anti-cadherin-11 mAb is in early clinical development for RA, further studies in patients with inflammatory arthritis are warranted. References: Sfikakis PP, Christopoulos PF, Vaiopoulos AG, et al. Cadherin-11 mRNA transcripts are frequently found in rheumatoid arthritis peripheral blood and correlate with established polyarthritis. Clin Immunol 2014;155:33–41. doi:10.1016/j.clim.2014.08.008. Disclosure of Interest: N. Vlachogiannis: None declared, P. Christopoulos: None declared, G. Bamias: None declared, K. Fragiadaki: None declared, M. Tektonidou: None declared, P. Sfikakis Grant/research support from: Educational grant from Janssen